Is the Clinical Diagnosis of Cutaneous Leishmaniasis Justified in Endemic Regions? - Al-Mendalawi , Mahmood D. (AL-Kindy College Medical Journal, 2023)
Leishmaniasis is a transmissible infection brought about by an obligatory intracellular protozoan from the genus Leishmania.  It occurs worldwide in tropical and subtropical regions and can be burdensome in resource-constrained countries. The infection ranges in severity from mild cutaneous lesions to more severe and sometimes life-threatening visceral and distorting mucocutaneous sicknesses. Importantly, cutaneous leishmaniasis (CL) is prevalent in the Middle East with a pooled prevalence of 12%. It imposes a significant health and socioeconomic burden